2022
DOI: 10.3390/nu14194086
|View full text |Cite
|
Sign up to set email alerts
|

Screen Time and Its Association with Vegetables, Fruits, Snacks and Sugary Sweetened Beverages Intake among Chinese Preschool Children in Changsha, Hunan Province: A Cross-Sectional Study

Abstract: (1) Introduction: Screen time may influence preschoolers’ food consumption. However, there is limited evidence regarding preschoolers, especially in China. The aim of this cross-sectional study was to investigate the association between screen time and the consumption of vegetables, fruits, snacks, and sugar sweetened beverages (SSBs). (2) Methods: Participants (1567 caregivers) were recruited from six kindergartens in Hunan, China. Caregivers completed the questionnaire, which included the food frequency ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Christofaro's study, conducted on students from Londrina in Brazil (14-17 years), showed a lower consumption of vegetables in both sexes associated with a screen time of more than 4 h per day compared with those respecting the recommendation of no more than 2 h per day [109]. Additionally, a cross-sectional study carried out on 1567 preschoolers (3 to 6 years) in China also reported a lower FV consumption and a higher consumption of snacks and sugar-sweetened beverages in children with longer screen time [111]. Again, a study conducted on 355 children (8-13 years) and 324 adolescents (14-18 years) from the Czech Republic highlights that regular FV intake was associated with higher odds of meeting the combination of PA and screen time in children and adolescents, and screen time and sleep recommendations in children only [116].…”
Section: Interactions Between the 24 H Movement Guidelines And Eating...mentioning
confidence: 93%
“…Christofaro's study, conducted on students from Londrina in Brazil (14-17 years), showed a lower consumption of vegetables in both sexes associated with a screen time of more than 4 h per day compared with those respecting the recommendation of no more than 2 h per day [109]. Additionally, a cross-sectional study carried out on 1567 preschoolers (3 to 6 years) in China also reported a lower FV consumption and a higher consumption of snacks and sugar-sweetened beverages in children with longer screen time [111]. Again, a study conducted on 355 children (8-13 years) and 324 adolescents (14-18 years) from the Czech Republic highlights that regular FV intake was associated with higher odds of meeting the combination of PA and screen time in children and adolescents, and screen time and sleep recommendations in children only [116].…”
Section: Interactions Between the 24 H Movement Guidelines And Eating...mentioning
confidence: 93%
“…Interestingly, eating order was also indicated to be associated with the risk of childhood obesity ( 9 ), as consuming vegetables first at a meal may not only reduce meal energy intake, but also increase vegetable intake ( 10 ). A survey of preschool children in Changsha, Hunan Province found that daily consumption of vegetables was reported by 64.4% of children ( 11 ). However, few studies have investigated the relationship between the eating order of meats/fish and vegetables, and childhood obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In England, for example, only 17% of boys and 19% of girls consume the recommended five or more servings of F&Vs per day [13]. According to a study conducted in Hunan, China, 35.6% and 42.4% of children aged 4-5 years consume vegetables and fruits more than once per day, respectively [14]. A Lebanese study found that only 17.8% of children consumed the recommended daily intake of vegetables, and only 34.3% consumed fruits daily [15].…”
Section: Introductionmentioning
confidence: 99%